# Question: What Is Sin 4x Equal To?

## What are the Trig identities?

In mathematics, trigonometric identities are equalities that involve trigonometric functions and are true for every value of the occurring variables where both sides of the equality are defined.

Geometrically, these are identities involving certain functions of one or more angles..

## What are the double angle formulas?

This unit looks at trigonometric formulae known as the double angle formulae. They are called this because they involve trigonometric functions of double angles, i.e. sin 2A, cos 2A and tan 2A. In order to master the techniques explained here it is vital that you undertake the practice exercises provided.

## What is sin 3x equal to?

sin(3x) = sin(x + 2x) Now use 1.

## What is sin 2x equivalent to?

By convention in Trigonometry, (sinx)2 is written as sin2 x, so # 3 is the correct answer.

## Does sin 3x 3sinx?

But leaving x = nπ, sin3X can almost almost equal to 3Sinx, making (sinx)^3 = 0. … So the smaller x coordinates for sin^3 will give nearly zero value.

## What is the Antiderivative of sin 3x?

Therefore integral of sin 3x is (1/3) (-cos 3x) + C.

## What is the formula of cos 3x?

The formula of cos(3x) is 4 cos^3(x) -3 cos(x).

## What is the formula of sin 4x?

Example:- sin 4x = sin2(2x) = 2sin2xcos2x=4sinxcosxcos2x.

## What is the value of sin 4x cos 4x?

Now,the maximum and minimum values of sin2x are +1 &-1 respectively . But here (sin2x)^2 is always positive so,the minimum value of(sin2x)^2 is 0. So ,the maximum value of sin^4x +cos^4x is 1–0=1(one).

## What is cos2x formula?

using the double angle formula. cos 2x = 1 − 2 sin2 x. = 2 sinxcos2 x + sinx − 2 sin3 x. = 2 sinx(1 − sin2 x) + sinx − 2 sin3 x. from the identity cos2 x + sin2 x = 1.

## What is cos4x?

hey friend the formula of cos4x is. = cos(2x)cos(2x) – sin(2x)sin(2x) = cos^2(2x) – sin^2(2x) = cos^2(2x) – (1 – cos^2(2x)) = 2cos^2(2x) – 1.

## What is 1 cos 2x equal to?

Cos2x is a double angle trigonometry that has the espansion of cos2x = cos^2(x) -sin^2(x) but you know that sin^2(x) + cos^2(x) = 1.